The Personified Petals: Communicating Self-Identity through Figurative Language in Noor Unnahar’s Poetry - Mauboy, Yemima Vanesha; Jayantini, I Gusti Agung Sri Rwa (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
Personification, a literary device that may give inanimate objects or abstract concepts life, has been used in poetry for an extended period of time. This research investigates the interesting realm of personification in a book of poetry in order to elicit more deep feelings, enrich thinking, and establish an intimate connection between the reader and the surroundings in a book of poetry Yesterday I Was The Moon (2017) by Noor Unnahar. In this study, twenty-two poetry titles were found that contain personification. This study uses the theory of figurative language by Kennedy & Gioia (1995). This research uses descriptive qualitative method where data was analysed and presented in discussion with detailed descriptions. The findings emphasize the importance of understanding the concept of self-identity wherein described from the attributes and things that are attached to a person. As well as the value of literature in understanding the characteristics of a poem based on the use of language and how a poem is interpreted with basic and general theories of language art. This study aimed to explore personification as a type of figurative language greater in depth. This investigation contributes to a growing number of studies on figurative language and semantic approaches to literature.